NEW ERA IN HIGHER EDUCATION : DIGITAL TRANSFORMATION AND INFORMATION SYSTEM MANAGEMENT - Raden Sintho Sukorini; Arita Marini; Rihlah Nur Aulia (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2024)
Abstract: This article aims to analyze digital transformation and the implementation of Management Information Systems (MIS) in higher education, particularly in the post-pandemic era. Through the Systematic Literature Review (SLR) method, the article reviews 10 relevant studies to understand the impact and challenges of technology implementation, such as Enterprise Resource Planning (ERP), in higher education institutions. The COVID-19 pandemic has accelerated the adoption of digital technologies, but many universities, especially in developing countries, face infrastructure and resource limitations. The article finds that while MIS can improve operational efficiency and learning, its implementation is still hindered by high costs and a lack of technical skills. The research gap identified is the absence of a holistic and sustainable implementation model in developing countries. As a novelty, the article proposes a collaborative model for MIS implementation, allowing multiple universities to share resources and knowledge. Furthermore, the article recommends the development of comprehensive digital transformation strategies that not only focus on technical aspects but also involve human resource management and data-driven decision-making. With this approach, higher education institutions can be better prepared to face future challenges and create a more inclusive and efficient educational experience.